The Orthopaedic Foot and Ankle Outcomes Research (OFAR) Network: Feasibility of a Multicenter Network for Patient Outcomes Assessment in Foot and Ankle. (September 2014) - Hunt, Kenneth J.; Alexander, Ian; Baumhauer, Judith; Brodsky, James; Chiodo, Christopher; Daniels, Timothy; Davis, W. Hodges; Deland, Jon; Ellis, Scott; Hung, Man; Ishikawa, Susan N.; Latt, L. Daniel; et al.
Introduction: There is an increasing need for orthopaedic practitioners to measure and collect patient-reported outcomes data. In an effort to better understand outcomes from operative treatment, the American Orthopaedic Foot & Ankle Society (AOFAS) established the Orthopaedic Foot and Ankle Outcomes Research (OFAR) Network, a national consortium of foot and ankle orthopaedic surgeons. We hypothesized that the OFAR Network could successfully collect, aggregate, and report patient-reported outcome (PRO) data using the National Institutes of Health (NIH) Patient Reported Outcomes Measurement Information System (PROMIS). Methods: Ten sites enrolled consecutive patients undergoing elective surgery for 1 of 6 foot/ankle disorders. Outcome instruments were collected preoperatively and at 6 months postoperatively using the PROMIS online system: Foot and Ankle Ability Measure (FAAM), Foot Function Index (FFI), and PROMIS physical function (PF) and pain computerized adaptive tests (CAT). During the 3-month period, 328 patients were enrolled; 249 (76%) had completed preoperative patient-reported outcomes data and procedure-specific data. Of these, 140 (56%) also completed 6-month postoperative patient- reported outcomes data. Results: Ankle arthritis and flatfoot demonstrated consistently worse preoperative scores. Five of 6 disorders showed significant improvement at 6 months on PF CAT and FAAM, 4 of 6 showed improvement on pain interference CAT, and no disorders showed improvement on FFI. Ankle arthritis and flatfoot demonstrated the greatest magnitude of change on most patient-reported outcomes scales. Conclusion: We were able to enroll large numbers of patients in a short enrollment period for this preliminary study. Data were easily aggregated and analyzed. Substantial loss of follow-up data indicates a critical area requiring further effort. The AOFAS OFAR Network is undergoing expansion with goals to ultimately facilitate large, prospective multicenter studies and optimize the quality and interpretation of available outcome instruments for the foot and ankle population. Level of Evidence: Level II, prospective comparative study.